An Experimental Study of P&O MPPT Control for Photovoltaic Systems - Badreddine Lahfaoui; Smail Zouggar; Mohamed Larbi Elhafyani; Mohammed Seddik (Institute of Advanced Engineering and Science, 2016)
Tracking the maximum power point plays an important role for the optimization of the solar energy. The objective here is to study experimentally optimizing photovoltaic (PV) systems connected to a DC-DC converter (Boost) and a resistive load. For this, tests were conducted to determine the law of open loop control (power versus the duty cycle) for different solar irradiance values and load with an approximately constant cell temperature. The obtained results showed that the power passes through a maximum point. In order to extract the maximum power, for different values of solar irradiance and load, an MPPT control